2014
DOI: 10.1158/0008-5472.can-14-0960
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-Mediated Repression of microRNA-101 Is Crucial for Inflammation-Promoted Lung Tumorigenesis

Abstract: Inflammatory stimuli clearly contribute to lung cancer development and progression, but the underlying pathogenic mechanisms are not fully understood. We found that the proinflammatory cytokine IL-1b is dramatically elevated in the serum of patients with non-small cell lung cancer (NSCLC). In vitro studies showed that IL-1b promoted the proliferation and migration of NSCLC cells. Mechanistically, IL-1b acted through the COX2-HIF1a pathway to repress the expression of microRNA-101 (miR-101), a microRNA with an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 48 publications
10
77
0
Order By: Relevance
“…Although the mechanisms by which IL-1β impacts lung tumor biology are not fully understood, our findings suggest that IL-1β exerts its pro-tumorigenic effects by promoting proliferation of lung epithelial cells. Our observations are consistent with a prior report that IL-1β increases proliferation of human NSCLC cells (Wang et al, 2014). …”
Section: Discussionsupporting
confidence: 94%
“…Although the mechanisms by which IL-1β impacts lung tumor biology are not fully understood, our findings suggest that IL-1β exerts its pro-tumorigenic effects by promoting proliferation of lung epithelial cells. Our observations are consistent with a prior report that IL-1β increases proliferation of human NSCLC cells (Wang et al, 2014). …”
Section: Discussionsupporting
confidence: 94%
“…Inflammation is a contributor to NSCLC progression [1012], and C5a can cause tumor cell proliferation [8, 9, 28, 29]. However, how C5a affects tumor cell proliferation in NSCLC still remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some pro-inflammatory factors such as IL-1 and IL-6 can upregulate C5aR expression during the process of other diseases [32, 33]. These factors, which also exist in NSCLC microenvironment [10], might elevate C5aR expression in NSCLC cells, and finally promoting NSCLC development and progression together with C5a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, its capacity to mobilize suppressive cells into the tumor microenvironment has been seen in genetically manipulated animals (34). The relevance of IL1b for cancer progression in humans has been demonstrated in melanoma (24) and non-small cell lung cancer (NSCLC) patients (35). The former study demonstrated that IL1b secreted by tumors carrying the BRAF mutation V600E promotes a PD-1 ligand-mediated suppressive effect in tumor-associated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%